Herbal Medicine: Clinical Perspective and Regulatory Status - Barkat, Md. A.; Goyal, Anjali; Barkat, Harshita A.; Salauddin, Mohammad; Pottoo, Faheem H.; Anwer, Esra T. (Combinatorial Chemistry & High Throughput Screening, 2021)
Herbal medicines play an important role in treating various ailments due to their potentially high therapeutic values and acceptability by patients with different health complications. The practice of herbal medicine involves the use of a part of a plant, the entire plant, or a selective isolated phytoconstituent. The search for new drugs during the scientific era revived the interest in the discovery of herbal drugs from different natural resources. The present modern healthcare system involves the utilization of drugs and 50% of them are of natural origin. In recent years, there had been an upsurge in the interest for search of novel herbal drugs by the pharmaceutical industry. However, the discovery of such new novel phytomedicines involves various challenges in the identification of active constituents; their characterization, pharmacological activity, toxicity/adverse effects, drug interactions, and, most importantly, their regulatory requirements. The present review is mainly focused on the history of herbal medicine, current clinical perspective, and pharmaceutical and regulatory challenges facing herbal drugs. Moreover, problems encountered in drug discovery from herbal resources and their possible solutions have been delineated.
Keywords: pharmaceutical industry